Porcentajes de sacarosa y harina de banano (musa paradisiaca) en la calidad del manjar a base de lactosuero como alternativa de aprovechamiento - Rodríguez Moreira, Johnny Fernando (2016)
The purpose of this research was to evaluate the effect of inclusion of different levels of sucrose and flour quality banana delicacy made from whey. The statistical design used was a bifactorial array 32. DCA nine treatments were developed, combining percentages of sucrose (18%, 20% and 22%) and banana flour (Musa paradisiaca) (1%, 2% and 3%) in relation to the experimental unit of 5 kg of whey, the methodology used to evaluate bromatológicos parameters were established in NTE INEN 0700: 2011, expressing test methods for total solids losses warming and the consistency assessed using the technique of medium consistency of Adams and sensory quality was assessed by semi-trained judges through a hedonic scale. With the results of the statistical program SPSS was established that the best treatment was T1 with a percentage of 18% sucrose and 1% banana flour, which obtained 19.08% in losses by heating; 84.77% total solids and 1.38 cm/s consistency, tabulation sensory data analysis resulted that although there are significant differences in color and taste, are within the range (I like) and ( I like) also I attribute smell not show significant difference, determining that the studied factors influence positively on the response variable.